Features of surgical treatment of chronic pancreatitis complicated by the syndrome associated with obstructive jaundice - S. V. Tarasenko; A. A. Natalskiy; O. D. Peskov; T. S. Rahmaev; I. V. Bakonina; A. Y. Bogomolov (Вестник хирургии имени И.И. Грекова)
Material and methods. The work is based on the results of retrospective analysis of data from the examination and treatment of 77 patients who were in the Center for Surgery of the Liver and Pancreas of the City Clinical Hospital of Emergency Medical Care in 2005–2017.Results. The article presents our analysis of the results of surgical treatment of patients with chronic pancreatitis complicated by obstructive jaundice.Conclusion. The obtained data allowed to substantiate the feasibility of preliminary minimally invasive decompression of the biliary tract, to determine its optimal method, as well as the choice of operational benefits in patients with subhepatic cholestasis.